The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1111/j.1523-536x.1997.00173.pp.x
|View full text |Cite
|
Sign up to set email alerts
|

“I Gotta Push. Please Let Me Push!” Social Interactions During the Change from First to Second Stage Labor

Abstract: Background: Forms of social interaction may occur among the participants in medicalized births, in which a woman in labor is experiencing strong involuntary urges to push but has not yet been found to have a completely dilated cervix. This article examines the social events and communications that occur at the change between first and second stages of labor: Method: Three cases are described from videotapes of women in the second stage of labor and their caregivers. Results: Severul social and interactive feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…the appropriate use of story prompts, continuers or silence) are being used as a tool to train midwives and other health caregivers in how to provide more effective support to women in crisis after childbirth (Kitzinger & Kitzinger, 2007). For video‐based studies of childbirth interactions that draw on CA, see also Bergstrom, Roberts, Skillman, and Seidel (1992) and Bergstrom, Seidel, Skillman‐Hull, and Roberts (1997).…”
Section: Contributions To Feminist/critical Workmentioning
confidence: 99%
“…the appropriate use of story prompts, continuers or silence) are being used as a tool to train midwives and other health caregivers in how to provide more effective support to women in crisis after childbirth (Kitzinger & Kitzinger, 2007). For video‐based studies of childbirth interactions that draw on CA, see also Bergstrom, Roberts, Skillman, and Seidel (1992) and Bergstrom, Seidel, Skillman‐Hull, and Roberts (1997).…”
Section: Contributions To Feminist/critical Workmentioning
confidence: 99%
“…Researchers from the Second Stage Labor Project (Roberts, McKay, Goodlin, Norr, & Seidel, 1989) described several social features of second stage labor (Aderhold & Roberts, 1991;Bergstrom, Roberts, Skillman, & Seidel, 1992;Bergstrom, Seidel, Skillman-Hull, & Roberts, 1997;McKay & Barrows, 1991;McKay, Barrows, & Roberts, 1990;McKay & Barrows, 1992;McKay & Smith, 1993). However, the focus of this study, the content and linguistic characteristics of birth talk, have not been described.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Most research on second stage labor has focused on physiological factors and procedures managed by caregivers, such as the nature of bearing down by women, positions to use for labor and birth, physiologic effects of bearing down on fetal oxygenation, and factors associated with perineal trauma (Roberts & Hanson, 2007;Roberts, 2002Roberts, , 2003Sampselle, Miller, Luecha, Fischer, & Rosten, 2005). Researchers from the Second Stage Labor Project (Roberts, McKay, Goodlin, Norr, & Seidel, 1989) described several social features of second stage labor (Aderhold & Roberts, 1991;Bergstrom, Roberts, Skillman, & Seidel, 1992;Bergstrom, Seidel, Skillman-Hull, & Roberts, 1997;McKay & Barrows, 1991;McKay, Barrows, & Roberts, 1990;McKay & Barrows, 1992;McKay & Smith, 1993). However, the focus of this study, the content and linguistic characteristics of birth talk, have not been described.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The purpose of the National Institutes of Health–funded grant was to describe care in second‐stage labor in enough detail so that care protocols could be developed and taught to obstetric personnel in order to conduct further studies on how care practices might affect clinical outcomes. The experimental phase of the project was never completed, but a large number of behavioral aspects of care in second‐stage labor were described, including specific social interactions, women's perceptions about labor, and caregivers' interpretations of sounds made by laboring women during the second stage 6–14 …”
Section: Literature Reviewmentioning
confidence: 99%
“…The experimental phase of the project was never completed, but a large number of behavioral aspects of care in second-stage labor were described, including specific social interactions, women's perceptions about labor, and caregivers' interpretations of sounds made by laboring women during the second stage. [6][7][8][9][10][11][12][13][14] Studies about women's levels of satisfaction regarding their childbirth experiences have not targeted second-stage labor, but indicate that women value factors such as individual attention from caregivers; caring, competent caregivers; communication; information; advocacy; pain relief and physical comfort; emotional support; and personal control. [15][16][17][18][19][20][21][22][23][24] Hodnett's 24 systematic review about women's satisfaction found that attitudes and behaviors of caregivers were the most powerful influences on how women rated their satisfaction with childbirth.…”
mentioning
confidence: 99%